Rodent acorn selection in a Mediterranean oak landscape (Ecological Research, 2006)
Quercus suber, Quercus ilex and Quercus coccifera (Cork, Holm and Kermes oaks, respectively) are common evergreen oak species that coexist in the landscapes of the western part of the Mediterranean basin. Rodents are the main acorn predators and thus one of the main factors for understanding recruitment patterns in oaks. In this paper we analyse to what extent mice prefer acorns from one oak species over another in three oak species studied using acorn removal experiments and video tape recordings. Twenty labelled acorns from each of the three Quercus species (60 acorns) were placed in 40 cm·40 cm quadrats on each plot. Because selection might vary as a result of the vegetation context, we performed the trials in the ﬁve main vegetation types within the study area (four replicates in each vegetation type) in order to control for habitat inﬂuences on rodent acorn preferences (a total of 20 plots). The removal of 1,200 acorns occurred within 68 days. Mice removed 98.7% of the acorns. Q. ilex acorns were preferred over Q. suber and Q. coccifera in all vegetation types except in pine forest, where no acorn preferences were detected. Acorn removal rates diﬀered with vegetation type, correlating positively with shrub cover. The distance at which acorns were displaced by rodents (mean =4.6 m±5.1 SD) did not diﬀer between acorn species, but varied among vegetation types. Bigger acorns of Q. coccifera were selected only after Q. ilex and Q. suber acorns were depleted, while no size selection was detected for the latter two species. Thus, we conclude that rodents show preference for some oak acorns and that landscape context contributes signiﬁcantly to rodent activities and decisions.